Re-interpreting rationalities of risky migration : Syrian refugees´ sea journeys to Europe Dance between wisdom and despair - Sunagic, Lejla (Division of Risk Management and Societal Safety, Faculty of Engineering, Lund University, 2026)
The thesis explores the migration experiences of Syrian refugees who arrived in Sweden and Denmark by crossing the Mediterranean Sea in small, precarious boats. It aims to illuminate how these refugees managed the risks they faced during their journey to Europe and the meanings they associated with these risks. The research focuses on the socio-cultural and individual contexts within which risk is perceived, experienced, and navigated, while recognizing the dynamic nature of risk. The thesis is guided by the central question: How did Syrian refugees construct their understanding of the risks associated with their clandestine journeys to Europe? The participants’ narratives provide insights into subjective factors that shaped their perceptions of risk and influenced their migration decisions—such as a desire for life change (as explored in Paper I) and a sense of commitment to their children's future (as discussed in Paper II). The analysis also reveals that participants' understanding of risk was fluid, evolving over time. It transpired that it was contingent on whether their risk assessment referred to the before migration or after the migrant, furthermore it changed depending on who the risk was being evaluated for (e.g., comparing their own risk-taking to that of others). Finally, the empirical studies challenged the traditional binary of rational versus non-rational approaches to understanding risk by revealing a nuanced interplay between these logics (Paper III). In the context of Syrian migration, it demonstrates that rational and non-rational modes of risk perception coexist dynamically and fluidly. The findings underscore the complexity of the decision-making processes of refugees engaged in clandestine migration and the difficult trade-offs they faced in pursuit of their goals. This research contributes to migration studies by highlighting the importance of subjective factors in understanding migration motivations and risk perceptions, thus challenging the dominance of structural explanations in the field. Furthermore, it contributes to much needed enlargement of frameworks through which risk research capture fluidity and of risk perception (Burgess, 2006).
Keywords: Refugees, migration, risk, perception, decision-making, rationality, subjectivity.